2001
DOI: 10.1007/s001980170047
|View full text |Cite
|
Sign up to set email alerts
|

Sodium is the Leading Dietary Factor Associated with Urinary Calcium Excretion in Hong Kong Chinese Adults

Abstract: We conducted a cross-sectional population-based study comprising 1010 Hong Kong Chinese (500 men and 510 women) aged 25-74 years during 1995-6. The study examined the important dietary, lifestyle and anthropometric factors associated with urinary calcium excretion. Dietary intakes were assessed by means of food frequency questionnaire. Spot urine was collected to measure the urinary excretion profiles of calcium (Ca), sodium (Na), potassium (K) and creatinine (Cr). When expressed as ratios of cations to urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Food items were those most frequently consumed based on previous local surveys [10], [11]. The food items and reference portion size (Chinese bowl) in our dietary records were similar to our previously validated one-week food frequency questionnaire [6]. Subjects received a 30-min training on estimation of food amounts, portion and utensil sizes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food items were those most frequently consumed based on previous local surveys [10], [11]. The food items and reference portion size (Chinese bowl) in our dietary records were similar to our previously validated one-week food frequency questionnaire [6]. Subjects received a 30-min training on estimation of food amounts, portion and utensil sizes.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies estimating salt consumption using timed urine samples, characterizing the food groups to assess contributions to the source of sodium as well as the associations with urinary sodium excretion are limited in Asian population. No study had been conducted among postmenopausal women with pre-hypertension or early hypertension, a population at high risk of cardiovascular diseases (CVD), declining renal function as well as osteoporosis (the major adverse medical conditions [4] [5] [6] linked with excessive sodium intake). Furthermore, potassium has been recognized as a protective factor for hypertension [7] and a proposed modifier of the association between sodium intake and CVD [8].…”
Section: Introductionmentioning
confidence: 99%
“…This has been confirmed in the Hong Kong Chinese population. 9 Increased urinary calcium loss predisposes to increased bone loss and osteoporosis. A direct connection may also occur through the calcium-dependent vasoactive properties of calcium-regulating hormones, which are linked to the activity of the rennin-angiotensin system.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive sodium intake increases the incidence of cerebrovascular and cardiovascular diseases due to high blood pressure [50]. It has also been reported that excessive sodium intake has an influence on obesity, gastric cancer, urolithiasis, and osteoporosis [51][52][53].…”
Section: Discussionmentioning
confidence: 99%